Investigating the Quality of Life on Farmer Family: Roles of Gender Relations, Economic Pressure, Financial Management, and Livelihood Strategies - Tin Herawati; Megawati Simanjuntak; Berti Kumalasari (Journal of Family Sciences, 2021)
Indonesia as the largest tropical agricultural countries support natural conditions make Indonesia a country rich in agricultural products. The objective of this research was to analyze the influence of economic pressures, financial management, gender relations, and livelihood strategies toward the farmer families quality of life. This research used a quantitative study design. The research took place in West Java. Sixty respondents were chosen from the farmer's wife that selected by using a simple random sampling. Data were collected directly using a structured questionnaire. Partial Least Square analyzed data. The results show that farmers' family economic pressure significantly affects livelihood strategy and quality of life, gender relations significantly affect livelihood strategy and financial management, and financial management significantly affects the quality of life. As suggestions, farmers families should further improve their livelihood strategies and financial management by understanding the importance of limited use of family resources. The implications for government are providing programs to improve quality of life, by forming cooperatives involving the role of farmers' wives.